خصائص تخدير مرضى كسور مفصل الورك - سلامة, عبد الهادي; يوسف, صفوان; جعبري, لما (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في مشفى الأسد الجامعي باللاذقية في قسم التخدير والإنعاش خلال العام 2007 ـ 2008 م، وتضمنت 120 مريضاً خضع كل منهم لعملية جراحية مصححة لكسر مفصل الورك وذلك تحت التخدير العام أو الناحي بما يناسب حالة المريض الصحية العامة وكانت نتائج الدراسة على النحو الآتي: 1ـ اعتبار مرضى كسور مفصل الورك مرضى عاليي الخطورة ويحتاجون لتداخل جراحي إسعافي خلال الأربع والعشرين ساعة بعد الإصابة. 2ـ إجراء العمل الجراحي بأنسب طرق التخدير (عام أو ناحي) بما يتناسب مع حالة المريض العامة والأمراض المرافقة وعدم ضياع الوقت في تحضيره لعدة أيام. 3ـ إذا كان المرض القلبي شديداً وغير معاوض (انخفاض شديد بالقلوصية القلبية، داء دسامات) نفضل عندها التخدير العام. 4ـ إذا كانت الإصابة التنفسية تمنع إجراء التخدير العام بصورة مطلقة فيجب عندها إجراء التخدير الناحي شريطة أن تكون وظيفة القلب التقلصية تسمح بنقل السوائل. This study was carried out in the Department of Anesthesia and Reanimation at AL- Assad University Hospital in Lattakia during the year 2007 – 2008 and included 120 patients; every patient had a reparative operation which was done under general or regional anesthesia according to his general health. The results are: 1- Hip joint fractures patients were considered as high risk patients and needed an emergency operation during twenty four hours. 2- The operation should be done under the best anesthesia according to the general health of the patient and other diseases without losing the time in preparing him for a few days. 3- If there were a high risk heart disease, we prefer the general anesthesia. 4- On the other hand, if there were a breathing disease we absolutely can not make the general anesthesia and we must do the regional anesthesia if the Ejection Fraction (EF) of the heart allows giving the patient a lot of liquid.